Faktor Yang Berhubungan dengan Pemanfaatan Deteksi Dini Kanker Serviks Metode IVA (Inspeksi Visual Asam Asetat) di Wilayah Kerja Puskesmas Kedungmundu Kota Semarang - Permatasari, Afina -; Setyawan, Henry; Udiyono, Ari; Sutiningsih, Dwi (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: VIA test is one of the early detection programs for cervical cancer in Semarang City. The usage of VIA is only 1.8% and only 42 WUS participated in the Kedungmundu Health Center in 2018.Objective: Objective of the study is to analyze the factors associated with the utilization of IVA examination aged 30-49th.Method: This study uses a quantitative method with a case control approach with 40 women of childbearing age participated IVA as cases and 80 women who have not participated IVA as controls.Results: factors associated to VIA test: fear (p = 0,0001; OR = 8,7; 95% CI = 3.67-20 87), Feeling Embarrassment (p = 0,0001; OR = 6.67; 95% CI = 2.87-15.48), family support (p = 0,0001; OR = 1.05; 95% CI = 0.01-1.38).Conclusion: fear, feeling embarrasement, family support are factors associated with participation in VIA test.